A study of the effect of body rotation on the arm push in shot put - Rahikainen, A.; Luhtanen, P. (Russian Journal of Biomechanics, 2004)
The aim of the research is to study the mechanics of the combined motion of the body rotation and the arm push, and to find the means to maximize the velocity of the shot generated during the arm push. The appropriate equation of shot motion was derived, and its solution was fitted into a measured velocity curve of the shot. The influence of the speed of body rotation on the length of the put was calculated and the optimal speed of body rotation was searched successfully. It was concluded that an effective means to increase the efficiency of the arm push could be to twist the direction of the shot`s path to the left at the beginning of the arm push. The speed of body rotation of the traditional slide technique was compared with the rotational technique. It was noticed that the speed of rotation of the traditional slide technique was 13.6 rad/s before the arm push, and it decreased to 10.8 rad/s during the arm push. Therefore, the essential thing seems to be that the exertion of the power of body muscles is so that the speed of body rotation does not decrease during the arm push.